2016
DOI: 10.1111/obr.12419
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic behaviours and depressive symptoms in children: a narrative literature review

Abstract: This review examines peer-reviewed, published articles exploring the role of obesogenic behaviours, including physical activity, screen time, and diet, and depressive symptoms, in 6- to 12-year-old children. Searches were conducted March-May 2014 and in August 2015 using PubMed, PsychInfo, and Embase. Eligible studies published between January 1990-August 2015 included 8- to 12-year-old children, any of the three previously identified obesogenic behaviours, and a measure of depressive symptoms. The search yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
(362 reference statements)
0
8
0
Order By: Relevance
“…Reviews of studies on very young children found low to moderate quality evidence that TV use is linked to unfavourable outcomes [35,44]. Systematic reviews examining older populations highlight that one in 8-12 studies find a null result, while the rest find a positive association between screen time and unfavourable psychological outcomes [13,58]. The relation is, however, not exceedingly clear.…”
Section: Systematic Reviews and Meta-analyses: Digital Technologiesmentioning
confidence: 99%
“…Reviews of studies on very young children found low to moderate quality evidence that TV use is linked to unfavourable outcomes [35,44]. Systematic reviews examining older populations highlight that one in 8-12 studies find a null result, while the rest find a positive association between screen time and unfavourable psychological outcomes [13,58]. The relation is, however, not exceedingly clear.…”
Section: Systematic Reviews and Meta-analyses: Digital Technologiesmentioning
confidence: 99%
“…In addition to physical inactivity and excessive food intake,9 many researchers have begun investigating the effects of psychological features such as depression on the development of obesity 10–18. Although symptoms of depression might lead to obesity theoretically because they are closely related to several key obesogenic risk factors—such as physical activity, daily screen time and dietary intake,19—empirical studies have not reached a consensus. For example, whether in clinical or non-clinical adolescent samples, depressed adolescents are at increased risk for development and persistence of obesity in the USA,14 20 but for Korean21 and Island Puerto Rican adolescents,22 overweight or obesity is not related to high levels of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…6 This rising prevalence is usually attributed to the recent economic progress which has been accompanied by certain demographic and nutritional transitions, urbanisation, and dietary and lifestyle changes. 5 7 Review of the epidemiological studies surrounding the determinants of overweight/obesity suggests attention is growing in regard to the impact of lifestyle related obesogenic behaviours. 8–10 Factors that appear most commonly include changing dietary choices, sedentary behaviour, watching TV, playing computer games, and level of physical activity (PA).…”
Section: Introductionmentioning
confidence: 99%
“…A growing consensus suggests a strong correlation between sedentary lifestyle and inadequate PA and the risk of developing NCDs. 7 9–11 Studies from low and middle income countries have shown that a large proportion of children and adolescents do not meet recommended levels of PA, as lifestyles involving higher PA have been displaced by more sedentary alternatives (satellite TV, computer games, telecommunication technology), thus contributing to reduced PA and energy expenditure. 12 It has been claimed that watching TV not only leads to reduced levels of PA, but involves a set of behaviours whereby sitting/lying is the dominant mode of posture with low energy expenditure, and that getting used to such postural behaviour can be replicated at school and in the workplace.…”
Section: Introductionmentioning
confidence: 99%